Design of Foundations for Offshore Wind Turbines - Bhattacharya, Subhamoy (John Wiley & Sons, 2019)
As the demand for "green" energy increases the offshore wind power industry is expanding at a rapid pace around the world. This book is a comprehensive reference which covers the design of foundations for offshore wind turbines, and includes examples and case studies. It provides an overview of a wind farm and a wind turbine structure, and examines the different types of loads on the offshore wind turbine structure. Foundation design considerations and the necessary calculations are also covered. The geotechnical site investigation and soil behavior/soil structure interaction are discussed, and the final chapter takes a case study of a wind turbine and demonstrates how to carry out step by step calculations.